Peran Penganggaran dalam Proses Pengambilan Keputusan di Tingkat Manajerial - Nurhasanah Nurhasanah; Elijon Tumanggor; Iman Putra Jaya Hulu (STIKes Ibnu Sina Ajibarang, 2025)
Budgeting plays a crucial role in organizational planning and control processes. This study aims to examine the strategic function of budgeting in managerial decision-making. Using a qualitative descriptive approach and literature review methodology, the study reveals that budgeting acts as a guide for resource allocation, performance evaluation, and uncertainty reduction in decision-making. Moreover, budgeting enhances interdepartmental coordination and managerial accountability. The findings confirm that budgeting is not merely an administrative procedure but a strategic instrument that supports the achievement of organizational goals.